PENERAPAN METODE PRAKTIKUM VIRTUAL BERBASIS SIMULASI PHET BERBANTUAN GUIDED-INQUIRY MODULE UNTUK MENINGKATKAN MATERI GELOMBANG PADA MATAKULIAH FISIKA - Agus Qowiyuddin; Kholifatur Rizqiyah (Universitas Nahdlatul Ulama Pasuruan, 2023)
This research aimed to determine the increase in student's physics content knowledge through the application of a virtual practicum method based on a PhET simulation assisted by the guided-inquiry module. The method used in this research was a classroom action research method. The research subjects were 1 class of students who took the Basic Physics course in odd semester of the 2022/2023 academic year. Collecting data method consisted of documentation, observation, survey, and test of content knowledge. The results showed that the average score of student content knowledge was 65 in the first cycle, 85 in the second cycle. The percentage of subject matter mastery obtained by the class was 50% in the first cycle, 100% in the second cycle. Based on these results, it can be concluded that there is an increase in student’s physics content knowledge after participating in learning with a virtual practicum method based on a PhET simulation assisted by the guided-inquiry module.